Transformasi Manajemen Pendidikan Islam di Era Digital: Kajian Literatur Tentang Kepemimpinan, Tata Kelola, dan Mutu Pendidikan - Nurul Aini; Muhammad Husni (Jurnal Manajemen dan Ilmu Administrasi, 2026)
Digital transformation has fundamentally changed the management of educational institutions, including Islamic education. These changes require educational institutions to develop adaptive management systems by strengthening leadership, governance, and educational quality. This study aims to analyze the transformation of Islamic educational management in the digital era through a literature review, focusing on the roles of leadership, governance, and educational quality. The study employed a qualitative approach using a library research design. Data were collected through documentation studies of scholarly journal articles, books, and relevant academic documents and were analyzed using content analysis to develop a conceptual synthesis. The findings indicate that digital transformation is not merely related to the adoption of information technology but also requires comprehensive changes in educational management systems. Successful transformation depends on adaptive leadership, transparent and accountable digital governance, and the readiness of human resources to implement innovation. The synergy among these elements contributes to improving organizational effectiveness, educational service quality, innovation culture, and the overall quality of Islamic education. This study proposes a conceptual framework positioning digital transformation as the primary driver for strengthening leadership, governance, and educational quality, thereby providing a theoretical and practical reference for the development of Islamic educational management in the digital era.